INCREASING PUBLIC PARTICIPATION TO PREVENT THE SPREAD OF COVID-19 IN DUKUH KUPANG SURABAYA - Winarno; Deny Arifianto; Myrna Adianti; Eva Inaiyah Agustin; Sisca Dina Nur Nahdliyah; Elsyea Adia Tunggadewi; Ali Suryaperdana Agoes (Jurnal Layanan Masyarakat (Journal of Public Services), 2022)
Novel Coronavirus 2019 (covid-19) is a generation of the coronavirus that humans have never identified. This virus was first reported to cause an outbreak in Wuhan, China, in December 2019. Until now, covid-19 infection cases have been reported in many countries, such as Thailand, Japan, South Korea, Iran, Italy, Germany, and more than 90 countries worldwide. Until November 1, 2020, a total of 412.784 positive cases of covid-19 were recorded, with 341.942 recovered patients and 13.943 deaths in Indonesia. The purpose of this event is to anticipate the spread of Covid-19 by reminding the public to maintain health protocols and other alternatives in preserving health, also increasing body immunity through massage and traditional Indonesian herbal medicine. This event received a good response from the public. It was evidenced by the number of participants exceeding the predetermined quota and enthusiastic in following the speaker's material. The event was a success and was well received by the participants as well as the local government. After following this event, participants can practise the knowledge obtained from the presenters to maintain and protect their health and immunity from Covid-19. Keywords: Covid-19, Community service, body immunity DAFTAR PUSTAKA Amri, Sofan. Iif Khoiru Ahmadi. 2010. Proses Pembelajaran Kreatif dan Inovatif Dalam Kelas: Metode, Landasan Teoritis-Praktis dan Penerapannya. Jakarta: PT. Prestasi Pustakaraya. Badan Pusat Statistik Kota Surabaya. “Jumlah RT RW Kecamatan Dukuh Pakis Menurut Kelurahan Tahun 2017”. surabayakota.bps.go.id. https://surabayakota.bps.go.id/statictable/2018/04/19/594/jumlah-rt-rw-kecamatan-dukuh-pakis-menurut-kelurahan-tahun-2017.html. (diakses 15 Desember 2020). Huang C, Wang Y, Li X, Ren L, Zhao J, Hu Y, Zhang L, Fan G, Xu J, Gu X, Cheng Z. 2020. “Clinical features of patients infected with 2019 novel coronavirus in Wuhan, China”. Lancet 2020: 395: 497-506. doi: https://doi.org/10.1016/S0140-6736(20)30183-5. Kementerian Kesehatan Republik Indonesia. 2020. Pedoman Kesiapsiagaan Menghadapi Coronavirus Disease (covid-19). Jakarta: Direktorat Jenderal Pencegahan dan Pengendalian Penyakit (P2P). Komite Penanganan Covid-19 dan Pemulihan Ekonomi Nasional. “Pasien Sembuh Harian Mencapai 4.141 Orang”. covid19.go.id. https://covid19.go.id/berita/pasien-sembuh-harian-mencapai-4141-orang. (diakses 15 Desember 2020). Kumar, M., & Dwivedi, S. 2020. “Impact of Coronavirus Imposed Lockdown on Indian Population and their Habits”. International Journal of Science and Healthcare Research Vol.5 Issue: 2: April-June 2020. ISSN: 2455-7587. Li, S., Wang, Y., Xue, J., Zhao, N., & Zhu, T. 2020. “The impact of covid-19 epidemic declaration on psychological consequences: A study on active weibo users”. International Journal of Environmental Research and Public Health, 17(6), 1–9. doi: https://doi.org/10.3390/ijerph17062032. Pemerintah Kota Surabaya, “Statistik”. lawancovid-19.surabaya.go.id. https://lawancovid-19.surabaya.go.id/visualisasi/graph. (diakses 15 Desember 2020). Rizma Riyandi. “Data Kecamatan Surabaya: Dukuh Pakis, Penduduk dan Wilayah”. ayosurabaya.com. https://www.ayosurabaya.com/read/2020/09/28/3230/data-kecamatan-surabaya-dukuh-pakis-penduduk-dan-wilayah. (diakses 15 Desember 2020). Zhu N, Zhang D, Wang W, Li X, Yang B, Song J, Zhao X, Huang B, Shi W, Lu R, Niu P. 2020. “A novel coronavirus from patients with pneumonia in China, 2019”. New England Journal of Medicine 2020: 382: 727-733. doi: 10.1056/NEJMoa2001017